Factors related to joining cooperatives for milk marketing among Spanish goat breeders - Sayadi S.; Calatrava J.; Ruíz F.A. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
Cooperative association is increasing among goat farmers to merge the goat-milk supply for trading, in order to establish fixed cost advantages and to obtain more added value from the milk along its marketing channel. This study seeks to identify factors related to cooperative marketing among goat-milk producers of south-eastern Spanish mountainous areas. From a sampling survey of 156 goat farmers, a third of whom have already joined cooperatives in order to sell their milk, different farm and farmer features have been considered in order to test the relationship with the fact of belonging, or not, to a trading cooperative. These features include: farm size, land use, breeder livestock training, type of labour employed, perspective of having continuity on farming, certain farm-management features. A binomial probit model has been formulated to identify factors related to the use of the cooperative trade. Finally, some conclusions have been drawn in this respect.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)